Tick saliva inhibits dendritic cell migration, maturation, and function while promoting development of Th2 responses - Skallová, Anna; Iezzi, Giandomenica; Ampenberger, Franziska; Kopf, Manfred; Kopecky, Jan (Journal of immunology (Baltimore, Md., 2008)
Similarly to other blood-feeding arthropods, ticks have evolved immunosuppressive mechanisms enabling them to overcome the host immune system. Although the immunomodulatory effect of tick saliva on several cell populations of the immune system has been extensively studied, little is known about its impact on dendritic cells (DCs). We have examined the effect of Ixodes ricinus tick saliva on DC function in vitro and in vivo. Exposure of DCs to tick saliva in vitro resulted in impaired maturation, upon CD40 or TLR9, TLR3 and TLR7 ligation, as well as reduced Ag presentation capacity. Administration of tick saliva in vivo significantly inhibited maturation and early migration of DCs from inflamed skin to draining lymph nodes, and decreased the capacity of lymph node DCs to present soluble Ag to specific T cells. Moreover, saliva-exposed DCs failed to induce efficient Th1 and Th17 polarization and promoted development of Th2 responses. Our data reveal a complex inhibitory effect exerted by tick saliva on DC function. Given the role of DCs as the key instigators of adaptive immune responses, alteration of their function might represent a major mechanism of tick-mediated immune evasion.
Keywords: lymfatické uzliny; antigeny CD40; klíště; Immune Tolerance; prezentace antigenu; Lymph Nodes; Saliva; Th1 buňky; CD40 Antigens; toll-like receptory; Th1 Cells; dendritické buňky; Cell Movement; Toll-Like Receptors; Animals; zvířata; Th2 Cells; pohyb buněk; myši; imunologická tolerance; Ixodes; sliny; Th2 buňky; Antigen Presentation; Dendritic Cells; Mice